(untitled) (Journal of Educational Management, 2023)
The study investigated the sources, effects and coping strategies of stress adopted by female employees with children in the University of Cape Coast. A descriptive study design was employed in carrying out the study. Two hundred and four (204) respondents were sampled out of the 431 female employees with children. The instrument used was a constructed questionnaire. The results revealed that demands from husbands, children and thinking of promotional issues were some of the stressors that confronted the respondents. The major effects of stress among the respondents were their inability to plan well and lack of concentration on household chores. The result showed that the most prevailing coping strategy adopted by the respondents was engaging in conversation with friends and family members as well as getting assistance from colleagues and house helps. It was concluded that female employees with children in the University of Cape Coast go through stress which emanates from different sources. Some of the recommendations were that management of the University should educate employees on appropriate strategies to cope with their stress and could be done through seminars, conferences and workshops on coping strategies of stress. Key Words: work stress, coping strategies, female employees, university of cape coast